Pedagogical practice of elementary school teachers in using the internet as a source of information for research, from the perspective of scientific literacy (Research, Society and Development, 2023)
The objective of this research is to identify the pedagogical practice of teachers in the 4th and 5th years of elementary school, using the internet as a source of information for research, from the perspective of scientific literacy. The work is characterized as descriptive and qualitative. The data collection instrument used is the semi-structured interview. Data analysis was carried out using the Discursive Textual Analysis (DTA) technique proposed by Moraes and Galiazzi. After applying the ATD, four categories emerged: Library; Internet Information Sources; Scientific research; and, Teaching and Learning. The results demonstrate that the sources of internet information that teachers use are websites, blogs, YouTube videos, links, textbooks and educational games. It is concluded that the study demonstrates the weaknesses of teachers regarding teacher training with regard to scientific literacy, research, use of sources and scientific rigor.